Higher wages and capital intensity: a closer look - Matti Viren (Aboa Centre for Economics (ACE), 2006)
This paper focuses on the relationship between higher wages and capital intensity. The relationship itself is by no means a novel finding but we try to provide a meaningful theoretical explanation for the relationship and empirical evidence on its exact nature. Our explanation is the outcome of the wage bargaining process in the case of capital-intensive companies. They are more vulnerable to strike threat than companies that have a small capital stock and thus they may more easily give in for union wage demand. In other words, the bargaining power of unions is related to the capital-labor ratio. This paper provides some tests for these hypotheses with an extensive panel data for Finnish unincorporated enterprises and companies. The results show the relationship between higher wages and capital intensity and very strong and it applies to all sorts of companies and, finally, and it is consistent with the wage bargaining hypothesis.
Keywords: J31; J51; 330; wages; bargaining; wage distribution; panel data